The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/s-0039-1687851
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages as Key Players during Adipose Tissue–Liver Crosstalk in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in Western countries that could lead to serious health problems including liver failure, cancer, or death. The term NAFLD includes a spectrum of disease states with histological features ranging from simple steatosis to nonalcoholic steatohepatitis (NASH). A key aspect within this research field is the identification of pathogenic factors that trigger inflammation, thus fueling the transition from nonalcoholic fatty live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 110 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…Similarly, in population with type 2 diabetes participating to the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, we could get the same conclusion at the baseline [28]. Furthermore, recent studies had shown that even within the normal blood glucose level, the higher HGI level may identify subjects with an increased risk of insulin resistance, carotid atherosclerosis [18], and fatty liver [17,29]. e rst study demonstrated the relationship between NAFLD and HGI in 1,120 white individuals without diabetes was in 2017.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, in population with type 2 diabetes participating to the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, we could get the same conclusion at the baseline [28]. Furthermore, recent studies had shown that even within the normal blood glucose level, the higher HGI level may identify subjects with an increased risk of insulin resistance, carotid atherosclerosis [18], and fatty liver [17,29]. e rst study demonstrated the relationship between NAFLD and HGI in 1,120 white individuals without diabetes was in 2017.…”
Section: Discussionmentioning
confidence: 54%
“…and liver cirrhosis, even hepatocellular carcinoma [29,31,32]. Furthermore, study had proved that methods reducing adipose tissue in ammation may improve insulin resistance in NAFLD [33].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the function of BAT at thermoneutrality might have an impact on HSC activation. Additionally, inflamed BAT also could release various factors into the systemic circulation, exposing liver tissue to inflammatory cytokines that might accelerate liver damage ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers focus on potential roles of the adipose tissue in NAFLD. In particular, adipose tissue macrophages were proposed as key players in NAFLD [146]. There is a general consensus that a large set of signaling molecules such as lipids, microRNAs, adipokines and immune-related compounds are released from adipose tissue into the portal vein triggering hepatic inflammation [146].…”
Section: Other Factors In Nafld and Nashmentioning
confidence: 99%
“…In particular, adipose tissue macrophages were proposed as key players in NAFLD [146]. There is a general consensus that a large set of signaling molecules such as lipids, microRNAs, adipokines and immune-related compounds are released from adipose tissue into the portal vein triggering hepatic inflammation [146]. In particular, the release of fatty acids from dysfunctional adipocytes results in liver parenchymal cell toxicity, which causes the ectopic accumulation of triglyceride-derived toxic metabolites increasing the activity of inflammatory pathways [147].…”
Section: Other Factors In Nafld and Nashmentioning
confidence: 99%